Research on the summer specialized training method of half-pipe snowboarding - Yang, C.-H.; Wang, B.-H.; Zhang, L.-T.; Liu, G.-B.; Liu, S.-M.; Guo, J.-L.; Zhang, H.-Q. (China Winter Sports, 2009)
For better preparing 2014 Olympic winter games and improving the scientization of summer specialized training of half-pipe snowboarding,the article has a research on the land specialized training method of half-pipe snowboarding in snowless season. Basing on the above study and practice,it theoretically discusses the causation of land specialized training method influencing the snowboarding technique. It suggests to develop the training equipment of improving training effect,to innovate the computer data system,to apply the evaluation system of video analysis and muscle work anatomy and biomechanics analysis in training effect. As a reference for coaches and snowboarders to improving the specialized training of half-pipe snowboaring,its purpose is to advance the development of half-pipe snowboarding.